Research Progress of Coal Damage under Unsteady Load in China - Xi Chen; Guoliang Ma; Chaonan Fan; Shaocheng Ge (Geofluids)
Coalbed methane mining, suppression of coal dust, and elimination of dynamic disasters are closely related to the expansion of coal body cracks and internal damage. Understanding the expansion mechanism of pore-cracks is critical to investigate coal body damage. In this study, research from 2016 to 2021 conducted on the coal damage mechanism in China was sorted and the progress in this field was analysed to systematically investigate coal body damage. Critical topics of research in this field in recent years were identified, and load types were classified into static and dynamic loads. Dynamic loads with obvious characteristics and considerable damage-increasing effects were classified into impacting, cyclic, pulsating, and other dynamic load types. The current load-generating devices, various detection techniques and methods, research results, and the future research directions under various load types were discussed. The current coal damage research is primarily based on macrocharacteristic analysis and the stage characteristics of characterisation variables. The use of scanning electron microscopy, computerised tomography three-dimensional reconstruction technology, and acoustic emission technology can reveal the pore propagation mechanism at the micro level.